Strength of basalt fibers influenced by thermal and chemical treatments. (January 2018) - Overkamp, Tim; Mahltig, Boris; Kyosev, Yordan
This paper presents an experimental investigation regarding the influence of the thermal and chemical treatment over the strength of one type industrially used basalt fibers. The fibers are heated at 160℃, 320℃, 480℃, 640℃, or 800℃ using a muffle furnace for 32, 64, 128, or 256 min. In the second series, the fibers are treated with 10% to 30% H2 SO4, HCl and NaOH aqueous solutions for 48 h. The strength of the fibers is tested after the different treatments and is found to be decreased even after moderate heating temperatures. The fibers are as well investigated by scanning electron microscopy and energy-dispersive spectroscopy. By energy-dispersive spectroscopic method, the surface composition of the fiber is determined and significant changes in composition are observed even after treatment at 160℃. Obviously the change in surface composition is related to the change in the strength. A possible explanation can be the decomposition of the sizing on the fiber surface.